Disney's World Cup: ESPN and the Un-Americanisation of Global Football. Issue 1 (1st October 2015) - Lewis, Jon
Abstract : This article examines the cultural politics of American soccer fandom, with specific attention paid to the ways in which the sport is positioned and platformed by the major sports networks, including, especially, cable television's biggest player in the United States, ESPN. The network's failure to exploit soccer as a marketable commodity can be traced to a persistent American futility at the sport on the international level, but it evinces as well a larger American cultural problematic, one in which ethnocentrism and isolationism is disguised, as it often is, as American exceptionalism.